Social Security Investment in Equities - Diamond, Peter; Geanakoplos, John (American Economic Review, 2003)
This paper explores the general-equilibrium impact of social security portfolio diversification into private securities, either through the trust fund or private accounts. The analysis depends critically on heterogeneities in saving, production, assets, and taxes. Limited diversification weakly increases interest rates, reduces the expected return on short-term investment (and the equity premium), decreases safe investment, increases risky investment, and increases a suitably weighted social welfare function. However, the effects on aggregate investment, long-term capital values, and the utility of young savers hinges on assumptions about technology. Aggregate investment and long-term asset values can move in opposite directions.